The Quality of Anti-SARS-CoV-2 T Cell Responses Predicts the Neutralizing Antibody Titer in Convalescent Plasma Donors - Kroemer, Marie; Boullerot, Laura; Ramseyer, Mélanie; Spehner, Laurie; Barisien, Christophe; Gravelin, Eleonore; Renaudin, Adeline; Cognasse, Fabrice; Gallian, Pierre; Hermine, Olivier; Lacombe, Karine; Tiberghien, Pierre; et al. (Frontiers in Public Health, 2022)
Convalescent plasma therapy has been described as an attractive approach to treat critically ill patients with COVID-19 (Coronavirus disease 2019). The selection of convalescent plasma donors (CPD) is commonly based on neutralizing antibody titer. A better understanding of the quality of immune responses following COVID-19 will enable the optimization of convalescent donors’ selection in convalescent plasma programs. The involvement of SARS-CoV-2 specific T cells in the induction and persistence of high affinity anti-SARS-CoV-2 neutralizing antibody is still poorly investigated. In this study, 115 CPD who presented SARS-CoV-2 and who were eligible for plasma donation were included. Comprehensive analysis of T cells together with humoral responses were performed in regards of sex, age and blood group type. High frequency of T cell responses against SARS-CoV-2 related protein such as spike glycoprotein (80.0%), nucleocapsid (NCAP) (70.4%) and membrane protein (VME1) (74.8%) were detected in CPD by ex vivo IFN- and TNF- ELISpot assays. Among CPD responders, most exhibited poly-specific T cell responses (75%) defined by the ability to mount a Th1 polarized response against at least two SARS-CoV-2 proteins. We found a positive correlation between the magnitude and the diversity of anti-SARS-CoV-2 T cell responses in CPD. Notably, both the magnitude and poly-specificity of SARS-CoV-2 T cell responses were highly correlated with neutralizing antibody titer in CPD. The present study highlights that the diversity and strength of SARS-CoV-2 specific T cell responses predicts neutralizing antibody titer following COVID-19. These observations show the interest to combine T cell assays and antibody titer for the selection of CPD and to a latter extend to assess COVID-19 vaccine efficacy in at-risk patients.